Electrical operation behavior and energy efficiency of battery systems in a virtual storage power plant for primary control reserve. (April 2018) - Betzin, Christopher; Wolfschmidt, Holger; Luther, Matthias
Highlights: Efficiency determination and investigation of two different battery storage systems. Framework consideration and analysis of energy efficiency of battery storage systems. Battery storage modeling with respect to influence on grid stability by primary control reserve. Abstract: A rising interest in battery systems for various applications needs a deep understanding of the system performance for technical and economical optimization. The electrical system behavior and the energy efficiency of two different Li-ion battery systems are presented in this paper. Both systems are designed for operation in a virtual storage plant with respect to the primary control reserve. The efficiency of both systems is analyzed including the battery, the power electronics and auxiliary units. Based on the overall energy efficiency of the electrical storage systems, a model is developed to show the impact on the operation and standby behavior. This model is transferred in a simulation framework investigating the application of battery systems towards primary control reserve. Real frequency data of continental European transmission system are used to simulate the behavior of the two systems in order to determine energy losses during operation. Primary control reserve is one possible application as grid support service for battery systems and is under current discussion. In this new field of battery application energy losses are a limiting factor for economic and technical qualification. The simulation identifies strengths and weaknesses of the investigated systems based on the determined efficiencies, and the results support an optimized operation strategy.